'One-pot' sequential enzymatic modification of synthetic glycolipids in vesicle membranes. Issue 11 (19th January 2018) - Craven, Faye L.; Silva, Joana; Segarra-Maset, Maria D.; Huang, Kun; Both, Peter; Gough, Julie E.; Flitsch, Sabine L.; Webb, Simon J.
Abstract : To create vesicles with cell-targeting coatings, two soluble enzymes were used to directly glycosylate vesicle surfaces in a 'one-pot' procedure. Abstract : β(1, 4)-Galactosyltransferase (β4Gal-T1) and T. cruzi trans -sialidase (TcTS) have been used in a 'one-pot' cascade to provide vesicles (liposomes) with a trisaccharide coating. These soluble enzymes catalysed the transfer of galactose then sialic acid onto a synthetic N -acetylglucolipid embedded in the bilayers. Clustering of this substrate into microdomains increased the rate of sialylated lipid production, showing that an increase in β4Gal-T1 activity is carried through the enzymatic cascade. These coatings modulated cell recognition. Hepatocellular carcinoma cells took up vesicles modified by β4Gal-T1 alone more extensively than sialylated vesicles produced by 'one-pot' sequential enzymatic modification.